The Impact Of Consumer Trust On Online Purchase Decisions In Indonesia - Abdul Wakil (PT. Anagata Sembagi Education, 2024)
The internet in the current era is no longer a medium for obtaining information and communication, but has become a necessity for every individual, including in terms of doing business. People in the current era use information technology to buy and sell goods or services via the internet. Online shopping is an activity of purchasing goods or services carried out via the internet. The difference between online and offline purchases is the mindset of consumers in analyzing a product they see so as to generate interest in the product and end up making a purchasing decision.The purpose of this research is to analyze the impact of consumer trust on online purchase decisions. The type of this research is a quantitative research using simple linear regression analysis. The population in this research are all Shopee marketplace consumers. The sampling method used in this research is purposive random sampling as many as 50 people. The results of this research show that consumer trust has a positive and significant effect on online purchase decisions.